The bookstore on the beach eaudiobook - Novak, Brenda (2021)
" A page-turner with a deep heart."—Nancy Thayer, New York Times bestselling author of Girls of Summer How do you start a new chapter of your life when you haven't closed the book on the previous one? Eighteen months ago, Autumn Divac's husband went missing. Her desperate search has yielded no answers, and she can't imagine moving forward without him. But for the sake of their two teenage children, she has to try. Autumn takes her kids home for the summer to the charming beachside town where she was raised. She seeks comfort working alongside her mother and aunt at their bookshop, only to learn that her daughter is facing a huge life change and her mother has been hiding a terrible secret for years. And when she runs into the boy who stole her heart in high school, old feelings start to bubble up again. Is she free to love him, or should she hold out hope for her husband's return? She can only trust her heart...and hope it won't lead her astray. "A heart-tugging romance. Readers are sure to be sucked in."—Publishers Weekly, starred review Don't miss New York Times bestselling author Brenda Novak's latest novel, The Seaside Library! Other charming reads from Brenda Novak: Summer on the Island One Perfect Summer